Dualism Between Human Rights and Public Interest in Using Mask During COVID-19 Pandemic - S, Michelle Angelika; Wijaya, Hanna; Firmansyah, Yohanes; Sylvana, Yana; Utomo, St. Laksanto (Interdisciplinary Social Studies, 2022)
Background: COVID-19's appearance, and subsequent pandemic, stunned the world. The spread is rapid, and research continues to this day, prompting the WHO and government to develop ever-evolving rules. The group can break the chain of COVID-19 disease transmission by implementing hygiene precautions such as wearing masks, washing hands with soap, bringing hand sanitizers, and maintaining distance, or what is commonly referred to as social distancing and independent isolation. Aim: As the title states, this research aimed to study the dualism between human rights and public interest in using mask during COVID-19 era. Method: This analysis employs a research methodology that includes a review of normative legal studies. Findings: Using a mask is a fundamental right that everyone has to breathe safe, virus-free air. Additionally, a mask promotes group rather than individual interests. As a result, the government acts by enacting legislation restricting the use of masks and enforcing other health protocols during this COVID-19 pandemic period, using sanctions to educate citizens about the importance of mask use today.